Heat transfer modification in an unsteady laminar boundary layer subject to free-stream traveling waves - Agarwal, Tapish; Cukurel, Beni; Jacobi, Ian (International journal of heat and mass transfer, 2024)
A laminar, thermal boundary layer was forced computationally by free-stream, traveling-wave velocity fluctuations and the effects on the wall heat flux and skin friction were measured as a function of the phase speed of the disturbances and the streamwise location along the developing flow. The heat flux modification due to the flow forcing was significantly higher than the corresponding skin friction enhancement, and the dependence of these two transport properties on the phase speed was qualitatively different. The skin friction modification exhibited a maximum at an optimal phase speed, which was explained in terms of the overlap of two distinct viscous layers within the boundary layer. The heat flux modification did not exhibit this maximum, although evidence was found to suggest such a maximum may occur with sufficient boundary layer development. Because the magnitude of the wall heat-flux modification scales quadratically with wave amplitude, traveling wave disturbances pose significant challenges for thermal transport measurements in periodically perturbed environments, like turbomachinery, but also new opportunities for the control of heat transfer. •Traveling wave perturbations affect skin friction and heat transfer.•Properties of traveling waves control the heat transfer change.•Unsteady heat transfer measurements can be biased by streaming.